Plasticity, Swell-Shrink, and Microstructure of Phosphogypsum Admixed Lime Stabilized Expansive Soil - Jijo James; P. Kasinatha Pandian (Advances in Civil Engineering)
The study involved utilization of an industrial waste, Phosphogypsum (PG), as an additive to lime stabilization of an expansive soil. Three lime dosages, namely, initial consumption of lime (ICL), optimum lime content (OLC), and less than ICL (LICL), were identified for the soil under study for stabilizing the soil. Along with lime, varying doses of PG were added to the soil for stabilization. The effect of stabilization was studied by performing index tests, namely, liquid limit, plastic limit, shrinkage limit, and free swell test, on pulverized remains of failed unconfined compression test specimens. The samples were also subjected to a microstructural study by means of scanning electron microscope. Addition of PG to lime resulted in improvement in the plasticity and swell-shrink characteristics. The microstructural study revealed the formation of a dense compact mass of stabilized soil.